GOSIP URIP: Information and Promotion System as a Support to Improve the Implementation of Orientation for New Inpatients in the Treatment Room at Kaliwates General Hospital, Jember Regency: Implementasi GOSIP URIP dalam Peningkatan Pelaksanaan Orienetasi Pasien Baru Rawat inap di Ruang Perawatan RSU Kaliwates Kabupaten Jember (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
New patient orientation is the process of accepting new patients and their families when new patients come for the first time. At the time of receiving new patients, it was conveyed about room orientation, treatment, medical, room order. From the results of the researcher's observations, nurses have not yet carried out the orientation of new inpatients. Because there are no guidelines and operational standards for procedures, flows and instruments. The new patient orientation aims to foster a relationship of mutual trust and initial information related to the nursing process, as well as room facilities, inpatient rooms and hospital procedures. Therefore, this community service activity is in the form of the GOSIP URIP program (New Inpatient Patient Orientation Movement). The innovation of this program consists of several innovations, namely the creation of guidelines, standard operating procedures, flows, and,instruments